Isolation and Characterization of Cellulase Enzymes from Marine Endophytic Fungi - Tarman, Kustiariyah; Hardiningtyas, Safrina Dyah; Mardiana, Rina; Isti'anah, Ismi; Salamah, Ella (Molekul, 2026)
ABSTRACT. Enzymes called cellulases can break down the β 1,4-glycosidic bonds in cellulose to produce glucose or simple sugars. In this study, marine endophytic fungi that were isolated from the seagrass Enhalus sp. were used to obtain cellulase enzymes, assess activity, and identify the ideal pH and temperature for cellulase enzymes. The research involved a number of steps for the isolation and characterization of cellulase enzymes from Enhalus sp. named EN marine fungi, including preparing the seaweed by soaking it in warm and room-temperature water, extracting the cellulase enzymes by cultivating the marine fungi on production media with pretreated seaweed, counting the total cellulase activity was assessed using the Mandels et al. (1976) technique, and purifying the cellulase enzymes by depositing it with ammonium sulfate at a saturation level of 30-80%. According to the findings, on day 9 with seaweed carbon as a source of warm water immersion, cellulase enzyme isolated from seagrass Enhalus sp. had the greatest crude extract activity of total cellulase enzyme activity (FPAse), amounting to 0.0276 U/mL. The cellulase enzyme precipitated at a 70% saturation level of ammonium sulfate with an FPAse activity of 0.0381 U/mL and a specific activity of 1.85 U/mg. At pH 5 and 50 °C, cellulase enzyme deposition in this investigation was at its best. Keywords: cellulase enzyme, extraction, Enhalus sp., seaweed